Sustainability Reporting and Its Impact on Financial Performance: Evidence from Indonesian Public Companies - Merry Anna Napitupulu; Duma Megaria Elisabeth; Septony B Siahaan; Januardi Mesakh (Jurnal Ilmiah Accusi, 2026)
This study aims to analyze the impact of sustainability reporting on the financial performance of public companies listed on the Indonesia Stock Exchange (IDX) for the period 2015–2024. A quantitative approach was adopted using secondary data from sustainability reports and annual financial statements of 120 non-financial companies listed on the IDX that published sustainability reports. Dependent variables include Return on Assets (ROA), Return on Equity (ROE), and Tobin’s Q, while the primary independent variable is the sustainability disclosure index measured using the Global Reporting Initiative (GRI) framework. Panel data analysis with fixed effects and random effects approaches was employed. Results indicate that sustainability disclosure has a significant positive effect on ROA (β = 0.214, p < 0.001), ROE (β = 0.187, p < 0.01), and Tobin’s Q (β = 0.312, p < 0.001), indicating that companies that comprehensively disclose sustainability practices have better financial performance and market value. These findings reinforce the literature on the positive relationship between environmental and social responsibility and firm value creation in the context of the Indonesian capital market